Fabrication and In Vivo Evaluation of In Situ pH-Sensitive Hydrogel of Sonidegib–Invasomes via Intratumoral Delivery for Basal Cell Skin Cancer Management - Maha M. Ghalwash; Amr Gamal Fouad; Nada H. Mohammed; Marwa M. Nagib; Sherif Faysal Abdelfattah Khalil; Amany Belal; Samar F. Miski; Nisreen Khalid Aref Albezrah; Amani Elsayed; Ahmed H. E. Hassan; Eun Joo Roh; Shaimaa El-Housiny (Pharmaceuticals)
Background/Objectives: Basal cell skin cancer (BCSC) develops when skin cells proliferate uncontrollably. Sonidegib (SDB) is a therapeutic option for the treatment of BCSC by inhibiting hedgehog signaling. The problems with SDB’s low solubility, poor bioavailability, resistance, poor targeting, and first-pass action make it less effective when taken orally. This investigation set out to design an intratumoral in situ pH-sensitive hydrogel of SDB-invasomes (IPHS-INV) that can effectively treat BCSC by improving SDB’s bioavailability, sustainability, targeting, and efficacy while also reducing its resistance and undesirable side effects. Methods: Numerous S-INV formulations were developed using Box–Behnken Design Expert and tested before settling on the optimum S-INV formulation. An experimental 7, 12-dimethylbenzanthracene (DMBA) carcinoma rat model was used for in vivo studies of the IPHS-INV formulation after it was combined with chitosan. Results: Phospholipids (1.72% w/w), cholesterol (0.15% w/w), ethanol (1% v/v), and cineole (1.5% v/v) were shown to be the optimal components in the SDB-invasome formulation. The IPHS-INV formulation outperformed the permeation and bioavailability of free SDB by 7.14 and 6 times, respectively, and sustained its release by 57.41%. The IPHS-INV formulation showed a decrease in tumor volume of 99.05% and a reduction of hypercellular tumors, indicating its anti-cancer activity. The intratumoral IPHS-INV formulation maintained a higher concentration of SDB in tumors, indicating its targeting activity. Conclusions: These findings support the use of the intratumoral IPHS-INV formulation as an effective strategy for the treatment of BCSC.